THE INFLUENCE OF HUMAN RESOURCES AND ORGANIZATIONAL CULTURE ON THE QUALITY OF ONE-DOOR INTEGRATED SERVICES AT THE BANDUNG HIGH COURT THROUGH JOB SATISFACTION AS A MEDIATION VARIABLE - Budyawan Herijanto; Vip Paramarta; Kosasih; Farida Yuliaty; Y. Ony Djogo; Fitriana (RADJA PUBLIKA, 2026)
This study aims to analyze the mediating role of job satisfaction in the influence of human resources (HR) and organizational culture on the quality of the One-Stop Integrated Service (PTSP) at the Bandung High Court. The background of this study is the persistence of public complaints regarding aspects of service speed and procedures, which indicates the need to strengthen internal organizational factors. This study uses a quantitative approach with an explanatory method. The research sample consisted of 103 employees determined using the Slovin formula from a total population of 137 people. Data were analyzed using path analysis with the help of IBM SPSS version 26. The results showed that HR and organizational culture have a positive and significant effect on job satisfaction and service quality. Job satisfaction was proven to have a significant effect on service quality. However, the Sobel test showed that job satisfaction does not act as a significant mediator in the relationship between HR and organizational culture on service quality. Organizational culture has a more dominant influence than HR. This finding confirms that improving service quality in judicial institutions is more effective if it is focused on directly strengthening HR and organizational culture, in addition to efforts to improve employee job satisfaction.